Analysis of the level of effectiveness of using a simple spinner machine to drain oil in pothils - Intan Zahrani Mufidah; Nisanty Eka Yuniar; Nur Alifah Kusumaningtyas; Siska Dwi Lestari; Eli Trisnowati (JTTM : Jurnal Terapan Teknik Mesin, 2024)
Pothil is a common regional dish from the Magelang region prepared with cassava. The peeling and frying of the cassava is the first step in the process of manufacturing pothil. People still utilize manual cooking oil drainers during the pothil frying process, which makes them ineffective at draining the oil. Using a dynamo, which is a device that transforms mechanical energy into electrical energy, one can create a basic spinner machine to assist with oil draining. The purpose of this study is to evaluate the efficiency of a basic spinner machine for draining oil from pots and to ascertain the correlation between rotation duration and oil production volume. This study used a quantitative experimental design, where oil volume was the dependent variable and rotation duration was the independent variable. An efficacy test utilizing oil paper to view the oil beams on the pothil was used to gauge how efficient utilizing a spinner machine would be. The study's findings indicate that when compared to turning the spinner machine for one or two minutes, a spinner machine that is rotated for three minutes can create the most oil—21 milliliters. Consequently, the longer the spinning period, the more oil is generated and the more successful the spinner machine is in lowering the oil content of the pothil